Keragaman M1 tanaman hias bunga matahari (Helianthus annuus l.) akibat iradiasi sinar gamma - Intan Novela Setya Monikasari; Syaiful Anwar; Budi Adi Kristanto (Journal of Agro Complex, 2018)
ABSTRACT The purpose of the research was to obtain the morphological variability of M1 sunflower ornamental plant and information of lethal doses (LD50) effect of mutation by gamma ray irradiation. The research was arranged in monofactor experimental with Completely Randomized Design (RAL) with 5 treatments and 5 replication, each replication consisted of 5 sunflower seeds was irradiated by gamma ray of 0, 5, 25, 45, and 65 Gy. The data observed were analyzed by anova and followed with BNT of 5% level. Parameters observed included germination, plant height, stem diameter, tube flower diameter, tape flower diameter, initiation time, perfect bloom age, chlorophyll, ribbon flower number, seed number, total seed weight, weight of 100 seeds, LD50, Flower color and heritability. The result showed that irradiation significant effected to plant height, stem diameter, tube flower diameter, ribbon flower diameter, initiation time, seeds number, seed weight, weight of 100 seeds. Lethal doses of sunflower is 74,19 Gy. Heritability value range from 23,47 to 73,81%.Keywords : Helianthus annus L., irradiation, LD50, heritability